The Dual Nature of Onuf’s Nucleus: Neuroanatomical Features and Peculiarities, in Health and Disease - Schellino, Roberta; Boido, Marina; Vercelli, Alessandro (Frontiers in Neuroanatomy, 2020)
Onuf’s nucleus is a small group of neurons located in the ventral horns of the sacral spinal cord. The motor neurons (MNs) of Onuf’s nucleus innervate striated voluntary muscles of the pelvic floor and are histologically and biochemically comparable to the other somatic spinal MNs. However, curiously, these neurons also show some autonomic-like features as, for instance, they receive a strong peptidergic innervation. The review provides an overview of the histological, biochemical, metabolic and gene expression peculiarities of Onuf’s nucleus. Moreover, it describes the aging-related pathologies as well as several traumatic and neurodegenerative disorders in which its neurons are involved: indeed, Onuf’s nucleus is affected in Parkinson’s Disease and Shy-Drager syndrome, whereas it is spared in Amyotrophic Lateral Sclerosis, Spinal Muscular Atrophy, Duchenne Muscular Dystrophy. We summarize here the milestone studies that have contributed in clarifying the nature of Onuf’s neurons and in understanding what makes them either vulnerable or resistant to damage. Altogether, these works can offer the possibility to develop new therapeutic strategies for counteracting neurodegeneration.